2018
DOI: 10.1097/prs.0000000000005066
|View full text |Cite
|
Sign up to set email alerts
|

Microtia in a Chinese Specialty Clinic Population: Clinical Heterogeneity and Associated Congenital Anomalies

Abstract: Background: Microtia is a congenital anomaly of the external ear that can appear in isolation or in association with other congenital anomalies. In this study, the authors identify the prevalence and phenotypes of associated congenital malformations in patients with microtia in a Chinese specialty clinic population. Methods: Data were collected from 672 patients seen between December of 2014 and February of 2016 in the Department of Auricular Reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The results of this study can complement our cognitive deficits in phenotypes associated with microtia. For example, the accompanying symptoms were mainly craniofacial abnormalities and musculoskeletal deformities in past studies, 5,6 whereas in this article nervous system defects accounted for a large proportion. It is speculated that the relatively cryptic symptoms of the nervous system and the complexity of the diagnosis may have contributed to the neglect during clinical evaluation.…”
Section: Disscusionmentioning
confidence: 50%
See 2 more Smart Citations
“…The results of this study can complement our cognitive deficits in phenotypes associated with microtia. For example, the accompanying symptoms were mainly craniofacial abnormalities and musculoskeletal deformities in past studies, 5,6 whereas in this article nervous system defects accounted for a large proportion. It is speculated that the relatively cryptic symptoms of the nervous system and the complexity of the diagnosis may have contributed to the neglect during clinical evaluation.…”
Section: Disscusionmentioning
confidence: 50%
“…The latter is often associated with abnormalities of other systems including craniofacial anomalies, limb defects, cardiovascular malformations, kidney dysplasia, thoracic abnormalities, and so on. [5][6][7][8][9][10][11][12] However, only a few phenotypic combinations are named as a defined syndrome based on the etiology found or several clinically recognizable symptoms that often occur together. For instance, a group of craniofacial abnormalities with microtia, facial asymmetry, ocular defects, and spinal deformities as typical phenotypes, was named Oculo-auriculo-vertebral spectrum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 85% of patients with CHARGE syndrome also had congenital heart defect (CHD). A recent study in the Chinese Han population showed that 44% of patients with microtia have one or more comorbid anomalies, including facial and neck (40%), followed by the musculoskeletal system (35%) and cardiovascular system (11%) [ 7 ]. A high incidence of CHD (3.35~18.5%) in microtia patients has been observed in multiple populations, but the potential genetic mechanisms underlying this association are still unclear [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microtia occurs more frequently in right side and males 4,5,44 About 40% of patients with microtia have other malformations or are part of a syndrome 6 . According to a research specified for Chinese, about 44% (293/672) of microtia patients had one or more associated congenital malformation, 7 which was consistent with previous research 6,8 . The common associated congenital malformations included preauricular skin tags, 8 facial nerve dysfunction, 9,10 spinal deformity, kidney malformation, limb malformation, cholesteatoma, 11 and CHD 12 …”
mentioning
confidence: 99%